2018
DOI: 10.1186/s12905-018-0644-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and decision-making with regard to pregnancy among HIV positive women in rural Maputo Province, Mozambique – a qualitative study

Abstract: BackgroundIn preventing the transfer of HIV to their children, the Ministry of Health in Mozambique recommends all couples follow medical advice prior to a pregnancy. However, little is known about how such women experience pregnancy, nor the values they adhere to when making childbearing decisions. This qualitative study explores perceptions and decision-making processes regarding pregnancy among HIV positive women in rural Maputo Province.MethodsIn-depth interviews and five focus group discussions with fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Isaac Maru, Rose Olayo, and Mary Kipmerewo of passage to womanhood, fertility test, identity and marital function [7] thus, women living with human immunodeficiency virus (HIV) desiring biological children is on the rise.…”
Section: Socio-cultural and Societal Demands Influencing Pregnancy Among Hiv Positive Women In Kakamegamentioning
confidence: 99%
“…Isaac Maru, Rose Olayo, and Mary Kipmerewo of passage to womanhood, fertility test, identity and marital function [7] thus, women living with human immunodeficiency virus (HIV) desiring biological children is on the rise.…”
Section: Socio-cultural and Societal Demands Influencing Pregnancy Among Hiv Positive Women In Kakamegamentioning
confidence: 99%
“…Almost all participants conceal their HIV status from professional staff as well as partners/family and friends. Lack of disclosure about HIV status due to lack of courage and stigma, especially diaspora in the African community, domestic violence, poor relations and fears of being abandoned by a partner (11)(12)(13)16) and discrimination in society (13,15,16) (17)…”
Section: Disclosure Of Hiv Statusmentioning
confidence: 99%
“…In several studies it was reported that there was no support from a husband or partner and family in treatment (11)(12)(13)(14)16), such as a prohibition by a husband to take HIV drugs (14). and inadequate economic, preventing them from taking medication (13).…”
Section: Womenmentioning
confidence: 99%
See 2 more Smart Citations